1995
DOI: 10.1111/j.1476-5381.1995.tb14902.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the presence of both pre‐ and postjunctional P2‐purinoceptor subtypes in human isolated urinary bladder

Abstract: 1 In order to characterize P2-purinoceptor(s) in human urinary bladder the contractile effects of ATP and its slowly-hydrolyzable analogues m,-methylene ATP (m,P-MeATP) and P,y-methylene ATP (P,yMeATP) were investigated on human detrusor strips taken from patients undergoing cystectomy for bladder carcinoma.2 Serial concentration-response curves (SCRC) for ATP, a,-MeATP and ,Iy-MeATP were constructed with an interval of 25 min between two successive doses to avoid tachyphylaxis. ATP (10 gM-10 mM) induced a pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
(29 reference statements)
3
12
0
1
Order By: Relevance
“…These contractile responses were rapid in onset, and the peak response was reached within a few (≤5) seconds. The concentration-response curve did not reach a plateau at the highest concentration tested, as previously reported (Palea et al 1995). The contractile responses to ATP were antagonized by both suramin and PPADS, in a concentration-dependent and insurmountable manner, with depression of the response to 1000 µM ATP (i.e.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…These contractile responses were rapid in onset, and the peak response was reached within a few (≤5) seconds. The concentration-response curve did not reach a plateau at the highest concentration tested, as previously reported (Palea et al 1995). The contractile responses to ATP were antagonized by both suramin and PPADS, in a concentration-dependent and insurmountable manner, with depression of the response to 1000 µM ATP (i.e.…”
Section: Resultssupporting
confidence: 48%
“…Recently, the contractile responses induced by ATP and a series of ATP analogues in the human bladder have been found to be mediated by P 2X - (Hoyle et al 1989;Palea et al 1995) as well as by separate P 2 -purinoceptors not identified yet (Palea et al 1995). In spite of the presence of excitatory purinoceptors on the effector cells, the presence of purinergic transmission in the human bladder is uncertain, with the cholinergic component accounting for nearly all the excitatory neuromuscular transmission (Andersson 1993;Hoyle and Burnstock 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the human detrusor muscle contains two contractile purinoceptor subtypes: one is activated by α,β-meATP and is probably a P2X receptor; the other receptor is activated by ADPβS and appears to be different from those which are included in the current classification system. In a later paper from this group [542], evidence was presented for prejunctional P2 receptors on parasympathetic nerve terminals as well as two postjunctional P2 receptor subtypes, one of which was insensitive to suramin. ATP-induced contractions were reduced about 30 % by indomethacin, indicating involvement of PGs, by 48 % after nifedipine and were abolished in Ca 2+ -free medium [323].…”
Section: Healthy Bladdermentioning
confidence: 99%
“…Существуют очевидные фармакологиче-ские доказательства наличия P2X-рецепто-ров в мочевом пузыре человека, где АТФ, α-β-метилен-АТФ, ADP-бета-S и динукле-отидные фосфаты вызывают сокращения [37][38][39][40]. Сокращения, вызванные АТФ, уг-нетались на 30% индометацином (что ука-зывает на участие простагландинов), на 48% -нифедипином (антагонистом мед-ленных кальциевых каналов), полностью исчезали в среде, свободной от кальция [38].…”
unclassified